Features of Female Teens from Empirical Perspective - Hoshovska, Daria; Hoshovskyi, Yaroslav (Psychological Prospects Journal, 2017)
The article highlights key approaches to the understanding of content and functional essence of the phenomenon self-acceptance. The paper analyzes the main scientific views on the issue self-acceptance of personality. Self- acceptance reveals the essential features in the context of the specific personal development of adolescent girls. It is marked that the selfacceptance as constituent of consciousness is the activity of personality, sent first of all to scalene realization of«Self», and also to the acceptance at the level of self-realization, unique subject. Self- acceptance is generally treated as a human activity of finding his    phenomenological«Self». This is a difficult emotional attitude towards herself, the perception and comprehension of it is formed as a result of self-acceptance and self-reflection. The self-acceptance is a versatile cognition and confession as the special processes of the individual`s psyches, which have sensory, volitional and other forms of display. It is marked that during ontogenesis of personality self-acceptance is stabilized together with cognitive by the managed many-sided character «I», by an adequate self- appraisal and comes forward as a certain mortgage of construction of balanced, positive self-image self-weighted. It is established, that the qualificatory line of acceptance is a presence of the positive setting in relation to herself, which is mostly formed first of all under act of external accepting options in relation to an individual in the process of his continuous socialization under various conditions. It has been established that self-acceptance of personality has cognitive, value, communicative, creative, aesthetic and other potential, takes place in stages and passes the same  stages as the objects of awareness of the outside world, that overcomes the way from elementary to self-acceptance and self-understanding, and finally to total self- acceptance. So self-acceptance is realized due to conglomerate through intellectual, speech, perceptual, material and others of human action. In the context of studying  the phenomenon of self-acceptance, particularly in the light of feminine self- acceptance, made an empirical study sample of adolescent girls who were studying in different types of educational institutions – secondary school and boarding school. The article also reveals the psychological characteristics of the negative impact of deprivation of identity, image and self-acceptance of personality. It is established  the specificity and ontogenesis and sociogeneza of deprived teenage girls , the main types of violations in self-acceptance are analyzed.Key words: consciousness, self, self-image, self-appraisal, self-acceptance, teenagers, girls-teens, comprehensive school, boarding school.